A gate tunable transmon qubit in planar Ge - Oliver Sagi; Alessandro Crippa; Marco Valentini; Marian Janik; Levon Baghumyan; Giorgio Fabris; Lucky Kapoor; Farid Hassani; Johannes Fink; Stefano Calcaterra; Daniel Chrastina; Giovanni Isella; et al. (Nature Communications)
Abstract Gate-tunable transmons (gatemons) employing semiconductor Josephson junctions have recently emerged as building blocks for hybrid quantum circuits. In this study, we present a gatemon fabricated in planar Germanium. We induce superconductivity in a two-dimensional hole gas by evaporating aluminum atop a thin spacer, which separates the superconductor from the Ge quantum well. The Josephson junction is then integrated into an Xmon circuit and capacitively coupled to a transmission line resonator. We showcase the qubit tunability in a broad frequency range with resonator and two-tone spectroscopy. Time-domain characterizations reveal energy relaxation and coherence times up to 75 ns. Our results, combined with the recent advances in the spin qubit field, pave the way towards novel hybrid and protected qubits in a group IV, CMOS-compatible material.